The Relationship of Digital Accounting and Digital Economics in Information Technology Transformation - Donny Teguh Santoso Junias; Deddy Barnabas Lasfeto; Fransiscus Nicodemus Naiola; Elma Margaretha Malelak (SAFE-Network, 2024)
The aim of this research is to conduct further studies related to the use of digital accounting in an effort to optimize the success of improving the digital-based economy so that it is hoped that it will actually provide real benefits for the business world without being accompanied by detrimental errors in management in the accounting field. The research method used is by conducting a questionnaire survey on several conceptual parameters in Digital Accounting that support the development of the Digital Economy in current conditions. Data analysis uses quantitative qualitative analysis to explain the results of the numerical data analysis produced. The sample used was 43 respondents taken randomly. The expected research output is to be able to make a strategic contribution to the use of digital accounting technology in supporting the development of the digital economy in the business world. The final conclusion of this research proves that digital accounting and the digital economy have a very strong relationship (Corr. Pearson=0.949141 > 0.80). Testing the correlation of digital accounting using the parameters of ease of information and data/internet access illustrates a very strong relationship with information transformation in the digital economic world.